Gambaran Upaya Pencegahan Stunting Di Dusun Kelapa Dua Kecamatan Kairatu Kabupaten Seram Bagian Barat - Epi Dusra (Universitas Muhammadiyah Manado, 2021)
Stunting (dwarf) is a condition where toddlers have less length and height compared to their age. This study aims to describe efforts to prevent stunting in toddlers. This research is a quantitative research with a descriptive design which was conducted in Dusun Kelapa Dua. The population in this study amounted to 40 people with a sample of 40 mothers. Sampling technique with total sampling, analyzed univariately. The results of the research analysis were known from 32 mothers, showing that economic status was < UMP, namely 82.5%, most mothers (30%) had a sufficient level of education, most mothers (45%) ) have sufficient knowledge. It was concluded that from the description of stunting prevention efforts, it was found that there were low prevention efforts in dealing with stunting problems.